Determinants of dog owner-charged rabies vaccination in Kinshasa, Democratic Republic of Congo - Kazadi, Eric Kawaya (PLoS One, 2017)
Rabies is a preventable fatal disease that causes about 61,000 human deaths annually around the world, mostly in developing countries. In Africa, several studies have shown that vaccination of pets is effective in controlling the disease. An annual vaccination coverage of 70% is recommended by the World Health Organization as a control threshold. The effective control of rabies requires vaccination coverage of owned dogs. Identification of the factors determining dog owners’ choice to vaccinate is necessary for evidence-based policy-making. However, for the Democratic Republic of Congo (DRC), the limited data on rabies vaccination coverage makes it difficult for its control and formulation of appropriate policies. A cross-sectional study was conducted in Kinshasa (Lemba commune) with dog-owning households and owned dogs as study populations. The association between dog vaccination and independent factors (household socio-demographics characteristics, dog characteristics, knowledge of rabies and location of veterinary offices/clinics) was performed with Epi-info 7. The Odds Ratio (OR) and p-value < 0.05 were used to determine levels of significance. A total of 166 households owning dogs and 218 owned dogs were investigated. 47% of the dogs had been vaccinated within one year preceding the survey which is higher than the critical coverage (25 to 40%) necessary to interrupt rabies transmission but below the 70% threshold recommended by WHO for control. The determinants of vaccination included socio-economic level of the household (OR = 2.9, p<0.05), formal education level of the dog owner (OR = 4, p<0.05), type of residence (OR = 4.6, p<0.05), knowledge of rabies disease (OR = 8.0, p<0.05), knowledge of location of veterinary offices/clinics (OR = 3.4, p<0.05), dog gender (OR = 1.6, p<0.05) and dog breed (OR = 2.1, p<0.05). This study shows that the vaccination coverage in this area can easily reach the WHO threshold if supplemented by mass vaccination campaigns.